Delegated Powers and Law Reform Committee : 71st Report, 2014 (Session 4) : Prisoners (Control of Release) (Scotland) Bill at stage 1.: 71st Report, 2014 (Session 4) : Prisoners (Control of Release) (Scotland) Bill at stage 1. (2014) - Scotland., Parliament., Delegated Powers and Law Reform Committee,
No abstract available